Fabrication and SERS properties of complex and organized nanoparticle plasmonic clusters stable in solution. Issue 28 (9th July 2020) - Blanco-Formoso, Maria; Pazos-Perez, Nicolas; Alvarez-Puebla, Ramon A.
Abstract : Controlled formation of hot spots in nanoparticle clusters endowed with colloidal stability results in reliable optical sensors capable of providing quantitative SERS responses. Abstract : SERS activity can be increased by the formation of hot spots at the interparticle junctions of plasmonic nanoparticles in very close proximity, dramatically improving the enhancement factors in comparison with isolated nanoparticles. Controlling the number and geometrical architecture of hot spots, while endowing the clusters with colloidal stability, results in feasible optical sensors, able to provide quantitative SERS responses. Here, we review the approaches proposed to date to produce colloidal stable clusters, focusing on the control of the coordination number of nanoparticle assemblies and interparticle gaps. Clusters of spherical nanoparticles of the same size and rods of the same size are described to subsequently outline core-satellite constructs of nanoparticles of different sizes. Besides, purification processes for nanoparticle clusters are revised to provide efficient production in high yields.